Developing Understanding of Critical Thinking Definitions, Concepts and Characteristics in TVET Higher Education - Sulaiman , Nor Lisa; Asmadi , Nor Aireen Shafira; Salleh, Kahirol Mohd; Hussein, Mahmood H. (Journal of Ecohumanism, 2024)
This study aims to provide an understanding of critical thinking skills in TVET higher education context by investigating the definition, concept, and characteristics of critical thinking skills that is appropriate for the context. Therefore, a data collection is done through an interview involving ten lecturers from TVET higher education institutions purposely to gather their insight, perspectives, and real practice on critical thinking skills. The interview data are analysed using thematic analysis. It was discovered that the critical thinking concept for the TVET higher education context is a decision-making process. Critical thinking is defined as reflective and reasonable thinking, and critical thinking characteristics are the ability to adapt and analyse other alternatives. From the result of thematic analysis, this study developed a conceptual framework of critical thinking skills concept, definition and characteristics for TVET higher education setting. The findings could provide a reference for TVET higher education lectures to understand and apply critical thinking skills during teaching. In addition, other researchers can use the findings to develop fundamental knowledge in exploring and researching critical thinking skills.